Development of Guided Inquiry Based Learning Materials Enriched with Augmented Reality in Electrolysis Cell Material - Pradani, Nevia; Munzil, Munzil; Muchson, M. (International Journal of Interactive Mobile Technologies (iJIM), 2020)
In electrolysis cell chemistry learning material students still experience Difficulties related to chemical material roomates characteristics include three levels of representation macroscopic, submicroscopic, and symbolic. Therefore, the chemistry should be taught by inquiry strategies must be supported a program that is Able to visualize particulate material aspects in an electrolytic cell, such as Augmented Reality. The purpose of this study was to produce guided inquiry-based teaching materials assisted by Augmented Reality on the topic of electrolysis cells. . The development of teaching materials is Carried out in three stages namely (1) analysis phase, (2) design phase, and (3) development stage. Teaching materials are validated by three expert validator. The results of the validation Obtained a percentage of 87. 6% for aspects of the assessment in terms of media, 86.1% for aspects of the assessment in terms of material and 87.4% for the readability test. This indicate that the chemistry teaching material that has been developed is included in the very feasible category so that it can be used as a support in learning activities electrolysis cell material